The effect of aquatic exercise on bone mineral density in older adults. A systematic review and meta-analysis - Schinzel, Eileen; Kast, Stephanie; Kohl, Matthias; von Stengel, Simon; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Lange, Uwe; Peters, Stefan; Thomasius, Friederike; Clausen, Jürgen; Uder, Michael; et al. (Frontiers in Physiology, 2023)
Aquatic or water-based exercise is a very popular type of exercise in particular for people with physical limitations, joint problems and fear of falling. The present systematic review and meta-analysis aimed to provide evidence for the effect of aquatic exercise on Bone Mineral Density (BMD) in adults. A systematic literature search of five electronic databases (PubMed/MEDLINE, Cochrane Library, Scopus, Web of Science and CINAHL) according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) was conducted until 2022/01/30, with an update to 2022/10/07. We included controlled trials with a duration of more than 6 months and at least two study groups, aquatic exercise (EG) versus non-training controls (CG) with no language restrictions. Outcome measures were standardized mean differences (SMD) with 95%-confidence intervals (95%-CI) for BMD changes at the lumbar spine (LS) and femoral neck (FN). We applied a random-effects meta-analysis and used the inverse heterogeneity (IVhet) model to analyze the data. Excluding an outlier study with an exceptionally high effect size for LS-BMD, we observed a statistically significant (p=.002) effect (EG vs. CG) of aquatic exercise for the LS-BMD (n=10; SMD: 0.30; 95%-CI: 0.11 to 0.49). In parallel, the effect of aquatic exercise on FN-BMD was statistically significant (p=.034) compared to the CG (n=10; SMD: 0.76, 95%-CI: 0.06 to 1.46). Of importance, heterogeneity between the trial results was negligible for LS (I2: 7%) but substantial for FN-BMD (I2: 87%). Evidence for risks of small study/publication bias was low for LS-BMD and considerable for FN-BMD. In summary, the present systematic review and meta-analysis provides further evidence for the favorable effect of exercise on bone health in adults. Due to its safety and attractiveness, we particularly recommend water-based exercise for people unable, afraid or unmotivated to conduct intense land-based exercise programs.